Measuring consumer outcomes: Development and testing of the Australian Community Care Outcomes Measure. (March 2017) - Cardona, Beatriz; Fine, Michael; Stebbing, Adam; Duncan, Cathy; Samsa, Peter; Eagar, Kathy
Abstract : Objectives: In the increasingly competitive environment of aged care in Australasia, how can providers and consumers be sure that the care support delivered is efficient and makes a positive difference? Monitoring outcomes has long been emphasised for ensuring quality service delivery, yet there is currently no consistently applied approach available. Methods: This paper considers the importance of measuring outcomes in community care and reports on the development and field trial of the Australian Community Care Outcomes Measure (ACCOM). The ACCOM combines data already collected by services on the capabilities and care needs of individual consumers and their demographic characteristics with a short questionnaire on quality of life based on the Adult Social Care Outcomes Toolkit (ASCOT). It is completed by consumers and staff. Results: In the first round of a field test of the ACCOM (2016), baseline data were successfully collected for over 200 individual aged care clients, each receiving consumer‐directed care (CDC) packages at home. Results show the measure to be practical and easy to use. A second round to measure change and enable the calculation of outcomes for each consumer was successfully completed 6 months later. Conclusion: Field testing of the ACCOM shows promising results. More extensive trials of the measure are planned across Australia.